2006
DOI: 10.1186/ar1864
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Dendritic cells (DCs) comprise heterogeneous subsets of professional antigen-presenting cells, linking innate and adaptive immunity. Analysis of DC subsets has been hampered by a lack of specific DC markers and reliable quantitation assays. We characterised the immunophenotype and functional characteristics of psoriatic arthritis (PsA)-derived and rheumatoid arthritis (RA)-derived myeloid DCs (mDCs) and plasmacytoid DCs (pDCs) to evaluate their potential role in arthritis. Circulating peripheral blood (PB) pDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
66
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(79 citation statements)
references
References 71 publications
10
66
1
Order By: Relevance
“…Although previously described as ''CD1c ? DC'' in rheumatoid arthritis synovial fluid [147][148][149], transcriptome analyses showed these cells to be most closely related to in vitroderived MoDC and of monocyte origin, and therefore the likely human equivalents of the mouse ''inflammatory'' DC [64]. These data provide evidence to suggest that inflammatory DC may be the main drivers of many autoimmune pathologies and may also contribute to tumor pathogenesis.…”
Section: Inflammatory DCmentioning
confidence: 61%
See 1 more Smart Citation
“…Although previously described as ''CD1c ? DC'' in rheumatoid arthritis synovial fluid [147][148][149], transcriptome analyses showed these cells to be most closely related to in vitroderived MoDC and of monocyte origin, and therefore the likely human equivalents of the mouse ''inflammatory'' DC [64]. These data provide evidence to suggest that inflammatory DC may be the main drivers of many autoimmune pathologies and may also contribute to tumor pathogenesis.…”
Section: Inflammatory DCmentioning
confidence: 61%
“…Myeloid DC infiltrate the inflamed tissues of many human autoimmune diseases including the epidermis and dermis of psoriatic lesions, synovial fluids of rheumatoid arthritis patients, and inflamed intestinal tissue in Crohn's disease patients [64,[146][147][148][149][150][151]. They can also be found in the ascitic fluid of patients with breast and ovarian cancers [64].…”
Section: Inflammatory DCmentioning
confidence: 96%
“…69 In RA, pDCs are decreased in circulation, presumably migrating preferentially into inflamed tissues. 10 This finding has also been observed in other diseases in which type I IFN has been implicated in pathogenesis, such as lupus 1113 and idiopathic inflammatory myositis. 14 Furthermore, previous studies have suggested that baseline type I IFN levels may predict treatment response in RA.…”
mentioning
confidence: 53%
“…The decrease of M-DC might be induced by migration of mature DC to the gut, the major site of T. whipplei infection, as described for Crohn's disease (34). However, apoptosis following chronic activation by high levels of circulating inflammatory mediators (23) or by a T. whipplei infection, as shown for macrophages (35), also might be responsible for reduced numbers of circulating DC, since elevated apoptosis markers have been described for serum of untreated CWD patients (36). During chronic disorders, circulat- (20), and, especially during inflammatory bowel disease, this might be triggered by microbial translocation through a leaky intestinal barrier.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 6-sulfo LacNAc DCs (slanDCs) were described as a source of IL-12 (17). Impaired T cell-stimulatory capacity has been demonstrated for DC infected with Mycobacterium tuberculosis (18), and alterations in the distribution and functionality of DC subsets have been described for various infections and chronic inflammatory diseases (19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Lassical Whipple's Disease (Cwd) Is a Chronic Multisystemimentioning
confidence: 99%